Shareholder Wealth Effects of Directors' Liability Limitation Provisions - Brook, Yaron; Rao, Ramesh K. S. (Journal of Financial and Quantitative Analysis, 1994)
The adoption of liability limitation provisions (LLPs) is associated with insignificant stock price reactions for all firms, but with positive stock price reactions for poorly performing firms. This result is consistent with the hypothesis that the net benefit of LLPs is larger for financially troubled firms than for other firms because outside directors are valuable to the distressed firm and LLPs substantially affect experts' expected costs of serving as directors of troubled firms.